Impact of perceived parenting style on emotional intelligence of nursing students - Singh, Harmesh; Singh, Ishneet; Soni, R. K. (International Journal of Contemporary Pediatrics, 2026)
Background: Emotional intelligence (EI) is multidimensional and includes components as perception of emotion, managing own emotions, managing others’ emotions and utilization of emotions. Perceived parenting style is how adolescents perceive their parent’s parenting styles as authoritative, authoritarian and permissive. There is paucity of data on impact of perceived parenting style on emotional intelligence of student nurses. Methods: This descriptive cross-sectional study included 178 nursing students. Ethical approval and informed written consent was obtained. They were assessed with the sociodemographic data sheet, a questionnaire-based perceived parenting style and the self-report EI scale. Analysis was done by descriptive analysis, ANOVA, Pearson correlation coefficient and p value ≤0.05 was taken as significant. Results: Majority of the participants were females. The mean age was 20.24±1.71 years. 61.2% were BSc students and 38.8% GNM. Majority were from rural background; 92.1% mothers were house wives and 77% of fathers were farmers. Education of mother had a significant impact on EI (p=0.052), managing own emotions (p=0.02) and managing others’ emotions (p=0.005). The perceived parenting styles by them was authoritative (87.1%), authoritarian (7.3%) and permissive (5.6%). Overall mean EI score was 122.53±10.65. Mean EI scores in authoritative, authoritarian and permissive parenting style of mothers were 123.05±10.44, 118.00±14.05 and 120.40±7.79, respectively as compared to 122.96±10.64, 119.38±11.54 and 120.79±9.95 in fathers. The effect of authoritative parenting style of mother was significantly high in managing others’ emotions (p=0.002) and utilization of emotions (p=0.002). Permissive parenting of mothers was negatively correlated with all components of EI except perception. Authoritative style of father had a significant effect on managing others’ emotions (p=0.012) and utilization of emotions (p=0.004). Conclusions: The impact of authoritative parenting style was significantly high in managing others’ emotions and utilization of emotions. Authoritarian style of father and permissive parenting of both the parents was negatively correlated with almost all components of EI except perception.